Inferring possible population divergence in Espeletia pycnophylla (Asteraceae) through morphometric and paleogeographic approaches - Benavides, Felipe; Burbano, Jorge; Burbano, Diana; Prieto, Rodrigo; Torres, Carlos (Revista de Biología Tropical, 2010)
The phenotypic structure within and between plant populations is generally influenced by their distribution patterns in space and time; therefore, the study of their divergence is a central issue for the understanding of their microevolutive processes. We boarded the hypothesis that three populations of Espeletia pycnophylla show phenotypic divergence as one of the possible implications of their geographic isolation in the Southern Colombian Andes. We used the Elliptic Fourier Descriptors (leaf shape) and traditional leaf morphometry (leaf size) of 347 leaves to measure inter and intra-population variation and a comparison between a paleogeographic reconstruction with an actual estimate of the distribution areas of E. pycnophylla in order to identify their main changes during the last 14 000 years. The three populations showed significant differences in leaf morphometry and a positive correlation between the matrices of morphometric and geographic dissimilarities, indicating that the inter-population divergence increases between further populations, so that the morphometric structure reflects their spatial distribution. The geographical and paleogeographical estimates evidenced a conspicuous process of reduction and fragmentation of the distribution area of E. pycnophylla since the Late-Glacial until the Holocene. We suggest that these results support possible scenarios of vicariance events, which allow us to approach the divergence of these populations in terms of their historic biogeographic relations. However, genetic analyses are still needed to support these results.